Blocking LINGO-1 in vivo reduces degeneration and enhances regeneration of the optic nerve. (4th April 2016) - Gresle, Melissa M; Liu, Yaou; Kilpatrick, Trevor J; Kemper, Dennis; Wu, Qi-Zhu; Hu, Bing; Fu, Qing-Ling; So, Kwok-Fai; Sheng, Guoqing; Huang, Guanrong; Pepinsky, Blake; Butzkueven, Helmut; et al.
Background: Two ongoing phase II clinical trials (RENEW and SYNERGY) have been developed to test the efficacy of anti-LINGO-1 antibodies in acute optic neuritis and relapsing forms of multiple sclerosis, respectively. Across a range of experimental models, LINGO-1 has been found to inhibit neuron and oligodendrocyte survival, axon regeneration, and (re)myelination. The therapeutic effects of anti-LINGO-1 antibodies on optic nerve axonal loss and regeneration have not yet been investigated. Objective: In this series of studies we investigate if LINGO-1 antibodies can prevent acute inflammatory axonal loss, and promote axonal regeneration after injury in rodent optic nerves. Methods: The effects of anti-LINGO-1 antibody on optic nerve axonal damage were assessed using rodent myelin oligodendrocyte glycoprotein experimental autoimmune encephalomyelitis (EAE), and its effects on axonal regeneration were assessed in optic nerve crush injury models. Results: In the optic nerve, anti-LINGO-1 antibody therapy was associated with improved optic nerve parallel diffusivity measures on MRI in mice with EAE and reduced axonal loss in rat EAE. Both anti-LINGO-1 antibody therapy and the genetic deletion of LINGO-1 reduced nerve crush-induced axonal degeneration and enhanced axonal regeneration. Conclusion: These data demonstrate that LINGO-1 blockade is associated with axonal protection and regeneration in the injured optic nerve.